Analysis of Social, Economic and Environmental Impacts on Village Communities Household Life after Mangrove Ecotourism Existence in Nira Nusa Village, Maurole District, Ende Regency - Patricius Marianus Botha; Yosefina Itu (Budapest International Research and Critics University, 2022)
The development process in various sectors will certainly be accompanied by the emergence of impacts that can be in the form of positive and negative impacts. The results showed that in the Nira Nusa village community, the condition of mangrove tourism which was relatively short in age had a serious effect on the spirit of tourism management for the local community. The condition of tourism which began to be neglected after being hit by a hurricane in 2021 made the entrepreneurial spirit of the local community gloomy and could even be said to be no longer growing. In many of the data summarized by the researcher, there are several things that are sampled as part of the percentage of the impact, both positive and negative impacts. First, on environmental conditions, that the people of Nira Nusa village when managing the tour slowly began to realize and understand the cleanliness of their environment both in the internal scope of the house and outside the household or in the house area. This awareness is built slowly because some visitors accidentally enter their homes and ask for a temporary ride to ask for some necessities or shopping for something. Cleanliness then becomes important research in their tourism development. This condition certainly did not last long due to the lata attitude of the community, namely the spirit that was driven by the mere profit factor. After the presence of Ecotourism in the midst of the community, the spirit remains and even continues to exist because there is a positive value but on the other hand, researchers also found that this power does not last long due to the impact of damaged tourism, minimal visitors and damaged tourist facilities have an impact on their enthusiasm for entrepreneurship. Again Garbage is then left alone, the yard of the house is not properly organized anymore, and environmental cleanliness is not a routine agenda that is programmed in joint activities. In addition to the environmental impact, it is also seen from the social impact and economic impact. From the observations and analysis made, the researcher found two important things in the social field.